Kemampuan Memecahkan Masalah Siswa Melalui Model Pembelajaran Auditory Intellectually Repetition berdasarkan Gender: (Student’s Problem-Solving Skills Through the Auditory Intellectually Repetition Learning Model Based on Gender) - Divani Syahida Luthfiah; Sistiana Windyariani; Setiono Setiono (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2023)
The ability to solve problems is important for student to meet the needs of the 21st century generation. This study aims to determine the effect of using the Auditory Intellecttually Repetition (AIR) learning model on students’ problom solving abilities based on gender. This research is a quasi-experimental reaserch with the reaserch design used is One Group Posttest Only. The sample of this research is high school students of class XI SMAN in Sukabumi City as many as 30 students. The result showed that there was an effect of the Auditory Intellectually Reperirion (AIR) learning model on students’ problem solving abilities. Goruping based on gender resulted in the percentage value of male students by 60% and the percentage value of female students by 54%, this means that the problem-solving ability of male student is higher than the probloem-solving ability of female students. The onclusion than can be drawn is that the Auditory Intellectually Repetition learning model can be used by teachers in training students’ problem solving skills. The ability to solve problems is important for student to meet the needs of the 21st century generation. This study aims to determine the effect of using the Auditory Intellecttually Repetition (AIR) learning model on students’ problom solving abilities based on gender. This research is a quasi-experimental reaserch with the reaserch design used is One Group Posttest Only. The sample of this research is high school students of class XI SMAN in Sukabumi City as many as 30 students. The result showed that there was an effect of the Auditory Intellectually Reperirion (AIR) learning model on students’ problem solving abilities. Goruping based on gender resulted in the percentage value of male students by 60% and the percentage value of female students by 54%, this means that the problem-solving ability of male student is higher than the probloem-solving ability of female students. The onclusion than can be drawn is that the Auditory Intellectually Repetition learning model can be used by teachers in training students’ problem solving skills. Key words: Auditory Intellectually Repetition (AIR), Problem Solving Ability, Gender ABSTRAK Kemampuan memecahkan masalah penting bagi peserta didik untuk memenuhi kebutuhan generasi abad 21. Penelitian ini bertujuan untuk mengetahui pengaruh penggunaan model pembelajaran Auditory Intellectually Repetition (AIR) terhadap kemampuan memecahkan masalah siswa berdasarkan gender. Penelitian ini adalah penelitian quasi eksperimen engan desain penelitian yang digunakan adalah One Group Posttest Only. Sampel penelitian ini adalah Siswa SMA kelas XI SMAN di Kota Sukabumi sebanyak 30 orang siswa. Hasil penelitian menunjukkan bahwa ada pengaruh model pembelajaran Auditory intellectually Repetition (AIR) terhadap kemampuan memecahkan masalah siswa. Pengelompokan berdasarkan gender menghasilkan data nilai persentase siswa laki-laki sebesar 60% dan nilai persentase siswa perempuan 54%, hal ini berarti kemampuan memecahkan masalah siswa laki-laki lebih tinggi dari kemampuan memecahkan masalah siswa perempuan. Kesimpulan yang dapat diambil model pembelajaran Auditory Intellectually Repetition ini dapat digunakan guru dalam melatihkan kemampuan memecahkan masalah siswa. Kata kunci: Auditory Intellectually Repetition (AIR), Kemampuan Memecahkan Masalah, Gender